2008
DOI: 10.1016/j.cell.2008.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 Suppresses a Caspase-2 Apoptotic Response to DNA Damage that Bypasses p53, Bcl-2, and Caspase-3

Abstract: Evasion of DNA damage-induced cell death, via mutation of the p53 tumor suppressor or overexpression of prosurvival Bcl-2 family proteins, is a key step toward malignant transformation and therapeutic resistance. We report that depletion or acute inhibition of checkpoint kinase 1 (Chk1) is sufficient to restore gamma-radiation-induced apoptosis in p53 mutant zebrafish embryos. Surprisingly, caspase-3 is not activated prior to DNA fragmentation, in contrast to classical intrinsic or extrinsic apoptosis. Rather,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
361
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(379 citation statements)
references
References 60 publications
(59 reference statements)
15
361
0
Order By: Relevance
“…Checkpoint kinase 1 (Chk1) was shown to suppress a caspase-2-dependent apoptosis pathway in p53-deficient cells. 37 Chk1 inhibition restored sensitivity to gamma-radiation-induced apoptosis independent of mitochondrial involvement and caspase-3. 37 This pathway is dependent on the ataxia telangiectasia-mutated (ATM) kinase, which upon activation by DNA damage phospho rylates the p53-induced death domain protein (PIDD), triggering the RIP-associated protein with a death domain (RAIDD) recruitment and assembly of the PIDDosome complex, leading to caspase-2 activation.…”
Section: Dna Damage Response (Ddr)mentioning
confidence: 91%
See 2 more Smart Citations
“…Checkpoint kinase 1 (Chk1) was shown to suppress a caspase-2-dependent apoptosis pathway in p53-deficient cells. 37 Chk1 inhibition restored sensitivity to gamma-radiation-induced apoptosis independent of mitochondrial involvement and caspase-3. 37 This pathway is dependent on the ataxia telangiectasia-mutated (ATM) kinase, which upon activation by DNA damage phospho rylates the p53-induced death domain protein (PIDD), triggering the RIP-associated protein with a death domain (RAIDD) recruitment and assembly of the PIDDosome complex, leading to caspase-2 activation.…”
Section: Dna Damage Response (Ddr)mentioning
confidence: 91%
“…37 Chk1 inhibition restored sensitivity to gamma-radiation-induced apoptosis independent of mitochondrial involvement and caspase-3. 37 This pathway is dependent on the ataxia telangiectasia-mutated (ATM) kinase, which upon activation by DNA damage phospho rylates the p53-induced death domain protein (PIDD), triggering the RIP-associated protein with a death domain (RAIDD) recruitment and assembly of the PIDDosome complex, leading to caspase-2 activation. 38 This Chk1-suppressed pathway has been proposed to be a mechanism of apoptosis that ensures deletion of cells that sustain DNA damage in the presence of compromised checkpoint surveillance.…”
Section: Dna Damage Response (Ddr)mentioning
confidence: 91%
See 1 more Smart Citation
“…Sidi et al (2008) reported that replication stress after DSB activates a different pathway where Chk1 suppresses a caspase-2-dependent apoptotic pathway. Chk1 inhibition hyperactivates ATM, ATR and caspase-2 after g-radiation and triggers a caspase-2-dependent apoptotic program that bypasses p53 deficiency and excess Bcl2 (Sidi et al, 2008). In addition, caspasemediated cleavage of Chk1 during apoptosis leads to enhanced apoptotic reactions (Okita et al, 2007;Matsuura et al, 2008).…”
Section: Dna Damage Induced Apoptosis and Role Of Chk1mentioning
confidence: 99%
“…In addition, Chk1 and Chk2 may be associated with the occurrence of glioma (Sancer et al 2004). Moreover, previous studies reported that loss of Chk1 sensitizes tumor cells to many anticancer agents (Wang et al 2004;Sidi et al 2008;Monica et al 2008;Morgan et al 2010). All these above mentioned suggest the key role of Chk1 and Chk2 enzymes in the cell cycle checkpoints activation, which in turn promotes the DNA damage repairing (Bao et al 2006), thereby preventing the cells from radiation and chemical therapy associated death.…”
Section: Discussionmentioning
confidence: 98%